Pemanfaan Model Evaluasi Belajar bagi Guru di SDN Tanjung Barat 08 Jakarta Menggunakan Quiz Creator - Rudi Hermawan (Universitas Indraprasta PGRI Jakarta, 2017)
Most students find a learning evaluation a bigissuebecause theyhave toreceive the learning evaluation by doing worksheetsin a tense atmosphere, leaving them with mixed feelings. Such can be turned into fun and interesting atmosphere for students if the teachers can take advantage of a computer-based technology. Learning evaluation can be performedby playing a guessing game, selecting pictures, arranging patterns, all of which can make students enthusiastic about doing their learning evaluation. The Quiz Creator is an application program that can make the interactive and fun learning evaluation. The Quiz Creator can be easily used in creating evaluation questions because the teachers do not need skill at a complicated programming to use it. Training and workshops that will be conducted forElementary School teachers are expected to encourage them to create interactive and fun learning evaluation materials. This is expected to make students more passionate about studyingbeforethe learning evaluation becausethe learning evaluation in classroom is conductedin fun and interactive ways.